Effect of Temperature, Time and Concentration using an aqueous sodium carbonate for degumming of silk fibroin Short Communication - Idris, Fadl elmoula Abdullah; Mohamed, Mutawakil; Abd Elwahab, Mohamed (Gezira Journal of Engineering and Applied Sciences, 2018)
ABSTRACT             The degumming process carried out to modify and control mechanical and biodegradable properties of silk fiber, it is defined as key factor for silk fiber treatment. The main objectives of this study are to evaluate the effect of temperature, times and caustic soda concentration on losses and recovery of silk fiber. The aqueous solution of Na 2 Co 3 was used; also the three reading for each (temperature, time and concentration) were taken. In order to evaluate the effect of each parameter on sciricn removed, one of these parameters should be variable and rest of parameters were kept constant. It has been obviously noticed the increasing of temp, aqueous concentration and time will increased the percentage of sericin removed. Result revealed that the effect of temperature on degumming loss percentage was higher at temperature range (60.70.80 and 90 0 C) the losses percentage recorded were (18, 21, 28 and 35 respectively) comparable with the degumming loss obtained by the effect of aqueous concentration and time. The study also showed that, when the values of concentration (0.01, 0.015. 0.02, 0.025g/l) and (20, 25 30, 35 min) were increased, the degumming loss were affected and increased linearly recorded values of (15, 22, 23, 26) and (16, 20, 25, 26) respectively. It is obviously noticed the optimum concentration, time and temperature which achieved higher sericin removed were (0.025g/l. 35 min and 90 0 C, respectively).